Effect of seed rate and N application rate in wheat blast resistant genotype BHU 35 under zero till condition - Sarkar, Pallab; Mitra, Biplab; Das, Saikat (Journal of Cereal Research, 2020)
A field trial was conducted under zero till condition during rabi, 2018-19 at the Instructional farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal located at 26Â°24â€™02.2â€N latitude, 89Â°23â€™21.7â€E longitude and 43 m above mean sea level. The experiment was designed in a two factor Randomized Complete Block Design. Three different levels of seed rate (125, 150 and 175 kg/ha) were factor 1, while three different levels of N application rate (120, 150 and 180 kg/ha) were factor 2 and these 9 treatment combinations were randomly allotted in each block, replicated thrice. The area of each experimental plot was 10 m Ã— 4.5 m. Sowing was done on 3rd December, 2018. The seeds were sown in lines 20 cm apart with 9 tyne zero-till-drill. The seed rate was adjusted based on treatment, while the basal fertilizer was applied uniformly irrespective of plots through complex complete fertilizer IFFCO (10-26-26). full P and K along with a portion of N (22.5 kg/ha) were applied as basal-furrow placement through zero till drill, while rest N (based on treatments) was applied in 2 equal splits during first and second irrigation. Altogether 3 irrigations were given at 20 days interval starting from 20 days after sowing (DAS).